#### Answer

(1;7)

#### Work Step by Step

vertex formula -b/2a
-(6)/2(-3) = 1
Substitute x = 1 into equation -3x^2 + 6x + 4
Therefore y = 7

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(1;7)

vertex formula -b/2a
-(6)/2(-3) = 1
Substitute x = 1 into equation -3x^2 + 6x + 4
Therefore y = 7

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.